(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2017)
The individuals who advance the idea of microfinance as a comprehensive improvement device accept that such unhindered access will help in neediness easing and uniform development. Different advances have been taken toward this path since Independence by Government, Financial Institutions, Microfinance Institutions, and NGOs which incorporate SHG-Bank Linkage Programmers as one such activity. Microfinance in J and K is still in its underlying stage from the formal sources like Public Sector Commercial Banks, District Cooperative Societies, Regional Rural Banks and Private Sector Commercial Banks, which give microfinance services to couple of thousand SHGs framed in the State and it is toward this path that the present investigation has been embraced. This examination completed in one of the Southern Districts of Kashmir endeavors to evaluate the job of microfinance in Self Help. The investigation is exact in nature and endeavors to break down the presentation of Self Help Groups regarding development, pay, improvement in expectations for everyday comforts, etc. The consequences of the examination demonstrate that microfinance has assumed a positive job to make Self Help Groups fruitful endeavors in the locale.